Effectiveness of Participatory Learning Strategies in Student Activity and Result in Fiqih’s Subject - Huda, Miftahul; Ahmad, Syarwani; Effendi, Darwin (Graduate Program Magister Manajemen Pendidikan, 2025)
This study examines the effectiveness of participatory learning strategies on the activeness and result of Fiqh. Quantitative experimental design with 40 students. Data collection techniques used questionnaires, observations, tests, and documentation. The validity test used construct validity while the reliability test used Cronbach's Alpha. The data prerequisite test used the normality test and parametric test, and the data was analyzed using a simple regression test. The results of this study indicate that: (1) there is significant effectiveness between participatory learning strategies and student’s liveliness with the results of R> p-value (0.467> 0.038). (2) There is significant effectiveness between participatory learning strategies and student’s result with the results of Y> p-value (0.324> 0.164). And (3) There is an increase in students' grades after using the Participatory Learning strategy when compared to students' mid-term exam grades on the subject of fiqh. Participatory strategies significantly increase activeness, but the effect on result needs further verification.